A comparison of aspirin against rivaroxaban for venous thromboembolism prophylaxis after hip or knee arthroplasty: A meta-analysis - Joshua Xu; Aran Kanagaratnam; Jacob Y Cao; Gurpreet S Chaggar; Warwick Bruce (Journal of Orthopaedic Surgery, 2020)
Purpose: Total knee arthroplasty (TKA) and total hip arthroplasty (THA) patients are at an elevated risk of post-operative venous thromboembolism (VTE). Newer thromboprophylactic agents such as rivaroxaban are increasingly used and effective in preventing thromboembolic events but may worsen bleeding risk. Recent studies have suggested that the more cost-effective aspirin may also be effective in preventing VTE. This systematic review and meta-analysis aimed to compare the efficacy of aspirin against rivaroxaban for the prevention of VTE following TKA and THA. Methods: Electronic searches were performed using five databases from their date of inception to August 2018. Relevant studies were identified, with data extracted and meta-analyzed from the studies. Results: Five studies were included, which consisted of 2257 in the aspirin group and 2337 in the rivaroxaban group. There were no differences between aspirin and rivaroxaban for either VTE ( p = 0.48) or its components deep vein thrombosis ( p = 0.44) and pulmonary embolism ( p = 0.98). Also, there were no differences between groups for either major bleeding ( p = 0.17), any bleeding ( p = 0.62), readmissions ( p = 0.37) or wound complications ( p = 0.17). Conclusion: Aspirin was not significantly different to rivaroxaban for prevention of VTE or adverse events after TKA or THA. However, this study was limited by the significant heterogeneity of the included studies. More large randomized studies are needed to add to this body of evidence.